2012
DOI: 10.4314/njp.v40i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Mothers and childhood pneumonia: What should the focus of public campaigns be?

Abstract: Background: Prompt administration of antibiotics to children with pneumonia significantly reduces the probability of death. However this requires early identification of such children in the community. In a country such as Nigeria with one of the highest pneumoniarelated deaths, what do mothers know about pneumonia, and what should be the content of public campaign messages? Methods: A structured questionnaire was administered to mothers attending paediatric clinics of Lagos University Teaching Hospital seekin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 14 publications
4
9
1
Order By: Relevance
“…Majority (87.1%) had poor knowledge of pneumonia causation, and (59.2%) reported that it was due to cold temperature and therefore keeping the child warm could help relief the symptoms. Similar findings were reported in a study done in Nigeria that cold caused pneumonia and reducing its exposure and wearing warm clothes would prevent it [27].…”
Section: Discussionsupporting
confidence: 89%
“…Majority (87.1%) had poor knowledge of pneumonia causation, and (59.2%) reported that it was due to cold temperature and therefore keeping the child warm could help relief the symptoms. Similar findings were reported in a study done in Nigeria that cold caused pneumonia and reducing its exposure and wearing warm clothes would prevent it [27].…”
Section: Discussionsupporting
confidence: 89%
“…This belief which is a common misconception among many lay people in Nigeria was also corroborated by the study in Lagos which found that 75.6% of mothers surveyed believed that cold was the main cause of pneumonia [15]. Furthermore, almost half of respondents in the present survey had knowledge of pneumonia vaccine with only 39.9% of these respondents having vaccinated their child against pneumonia.…”
Section: Discussionsupporting
confidence: 76%
“…This is hardly surprising as caregivers with these sociodemographic variables are more likely to have more experiences of childhood illnesses and/or are better informed about pneumonia. A hospital based study in Lagos University Teaching Hospital affirmed this finding [15]. It showed that caregivers with lower than tertiary education were more likely to have less knowledge on aspects of pneumonia disease.…”
Section: Discussionmentioning
confidence: 90%
“…As far as the education level of a mother is concerned, our study participants were more literate 40.8% as compared to other study has only 32.6% literacy level (13). Although we did not compare the association of mothers' education level with their knowledge, another study has shown that there is the positive association between them (15). The current study found that more than 50% mothers were able to identify the cause and related factors, which contribute towards pneumonia.…”
Section: Discussioncontrasting
confidence: 58%